2021
DOI: 10.1155/2021/8010391
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sound Absorption Properties in Polyurethane Foams by the Inclusion of Al2O3 Nanoparticles

Abstract: At present, the scale of China’s power grid is becoming larger and larger, and the control of low-frequency noise in substations (especially for transformers) is very important. The sound-absorbing materials have become one of the important ways to control low-frequency noise. The single polyurethane material cannot satisfy the requirements for reducing low-frequency noise, so it is very necessary to study its composite with other materials. In the paper, the flexible polyurethane foam and Al2O3 nanoparticle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…3a , it can be observed that the pure PUF has a highly porous 3D-hierarchical structure made up of open pore channel similar to a polyhedral model and inter-connecting framework. This morphology is similar to that previously reported in the literature (Farukh and Dhawan 2016 ; Gavgani et al 2016 ; Yuan et al 2021 ). Figure 3b shows that the as-prepared UGCN exists as large aggregates composed of several ultrathin layered two-dimension sheets with a thickness of few nanometers and irregular slightly curled edges.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3a , it can be observed that the pure PUF has a highly porous 3D-hierarchical structure made up of open pore channel similar to a polyhedral model and inter-connecting framework. This morphology is similar to that previously reported in the literature (Farukh and Dhawan 2016 ; Gavgani et al 2016 ; Yuan et al 2021 ). Figure 3b shows that the as-prepared UGCN exists as large aggregates composed of several ultrathin layered two-dimension sheets with a thickness of few nanometers and irregular slightly curled edges.…”
Section: Resultssupporting
confidence: 92%
“…On the other side, the XRD pattern of pure PUF shows the presence of a broad peak at 20.4° which indicates the amorphous nature of the prepared PUF. Notably, the obtained XRD pattern is typical for isocyanate-based PUF (Farukh and Dhawan 2016 ; Kim et al 2018 ; Yuan et al 2021 ). The composite material (PUF/UGCN) has three diffraction peaks at 13.5°, 19.0°, and 27.2°.…”
Section: Resultsmentioning
confidence: 81%
“…The Al 2 O 3 -PU composites were prepared according to the research methods previously published by our team 13 The Al 2 O 3 -PU foam and plexiglass were bonded by the epoxy resin and curing agent with a ratio of 5:1, and then was dried naturally for more than 12 h. The diameter of composite structure was 100 mm, and the thickness of plexiglass was 5 mm. The spacing of holes with a diameter for 2 mm on the perforated top cover was 10 mm, and the perforation rate was 2.44%.…”
Section: Methodsmentioning
confidence: 99%
“…The air part of the pipe was endowed with air characteristics, and the sound-absorbing material part was endowed with Al 2 O 3 -PU porous foam properties. The parameters of Al 2 O 3 -PU foam were as follows: porosity 0.704, flow resistance 70,000 N·s·m −4 , tortuosity factor 1.34, viscosity characteristic length, 1.99 × 10 −5 m, thermal characteristic length 4.64·10 −5 m. 13,14 A perfect matching layer was applied to the left air region. And each small hole of the regular plexiglass circular plate was filled with an air column.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation